SUN-687 MODY-14: A Rare Cause of Inherited Diabetes - Epp, Riley (J Endocr Soc, 2020)
Case: A 29-year-old physically active, lean man presented with a three-year history of poorly controlled diabetes diagnosed during a flu-like illness and no history diabetic ketoacidosis. Despite treatment with various oral hypoglycemic medications his glycated hemoglobin was consistently above target (never falling below 9.3%) and correlated with home blood glucose readings. His mother had gestational diabetes with all three of her pregnancies. His maternal grandmother was also known to have diabetes. Pancreatic islet antibodies were negative. C-peptide levels were low. Monogenic diabetes (MODY) was suspected. Discussion: Genetic testing revealed a mutation in the Adaptor Protein, Phosphotyrosine Interaction, PH domain, and leucine zipper containing 1 (APPL1) gene. APPL1 is involved in insulin secretion and insulin signaling via the Akt pathway [1,2,3]. Other mutations of APPL1 causing MODY-14 have been previously described [4]. In our case, the substitution of glutamate for aspartate at the 265 position occurs within the unique fourth alpha helix of the BAR domain of APPL1 [5]. Generally, BAR domains contribute to APPL1 dimerization and plasma membrane association [5]. Substitution of glutamate could disrupt protein folding, impairing dimerization and phosphorylation of Akt, thereby decreased insulin secretion as seen in other mutations of the BAR domain of APPL1 [4]. Although this remains a hypothesis, loss-of-function of APPL1 would explain the lack of insulin secretion without evidence of pancreatic autoimmunity. If the hypothesis is correct, it would be a novel mutation attributable to this MODY subtype. 1. Cheng KKY, Lam KSL, Wu D, et al. APPL1 potentiates insulin secretion in pancreatic β cells by enhancing protein kinase Akt-dependent expression of SNARE proteins in mice. Proc Natl Acad Sci U S A. 2012;109(23):8919–8924. doi:10.1073/pnas.1202435109 2. Ryu J, Galan AK, Xin X, et al. APPL1 potentiates insulin sensitivity by facilitating the binding of IRS1/2 to the insulin receptor. Cell Rep. 2014;7(4):1227–1238. doi:10.1016/j.celrep.2014.04.006 3. Saito T, Jones CC, Huang S, Czech MP, Pilch PF. The interaction of Akt with APPL1 is required for insulin-stimulated Glut4 translocation. J Biol Chem. 2007;282(44):32280–32287. doi:10.1074/jbc.M704150200 4. Prudente S, Jungtrakoon P, Marucci A, et al. Loss-of-Function Mutations in APPL1 in Familial Diabetes Mellitus. Am J Hum Genet. 2015;97(1):177–185. doi:10.1016/j.ajhg.2015.05.011 5. Li J, Mao X, Dong LQ, Liu F, Tong L. Crystal Structures of the BAR-PH and PTB Domains of Human APPL1. Structure. 2007;15(5):525–533. doi:10.1016/j.str.2007.03.011